Towards the Assessment of Viceroy Mikhail Vorontsov’s Cultural-enlightenment Policy - Tamaz Jologua (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2011)
The assessment of Viceroy Mikhail Vorontsov’s (1844-1854) “Caucasian policy” differs diametrically – from highly positive (D. Qipiani, A. Tsereteli, M. Shcherbinin, M. Makievski-Zubok, A. Jorjadze, M. Tamarashvili, Sh. Amirejibi, S. Qubaneishvili…) to to extremely negative (N. Avalishvili, M. Katkov, V. Kotetishvili, L. Asatiani, G. Abzianidze, R. Chkheidze, N. Vakhania…). A special study of the issue has shown that Vorontsov arrived in the Caucasus with a basically thought out reformist plan, envisaging the political and economic merger of Georgia (and the Caucasus in general) in the Russian empire, and at the same time revival of Georgian culture through Europeanization. The practical implementation of the Viceroy’s plan in 1840-1850 brought about highly significant transformation of the social and cultural enlightenment life of Georgia, and intensive and irreversible Europeanization of the country. A purposeful and planned cultural-enlightenment policy, launched with Vorontsov’s support and the decisive participation of Georgian public figures, gave rise to a process that was crowned with the creation and establishment of a national ideology, based on the world view and literary principles, clearly formulated by I. Chavchavadze (generally by the “Tergdaleulis”) in the 1860s.